Status of woodland caribou in Ontario: 1996 - Cumming, Harold G. (Rangifer, 1998)
Over 20 000 woodland caribou were reported in Ontario during 1966, the highest figure ever published. Photographic counts of the Pen Islands herd, bordering Manitoba, have shown constant increases from 2300 in 1979 to 10 800 in 1994. Elsewhere in Ontario, estimates have been declining, from 13 000 in 1965 to 11 000 in 1989 to under 10 000 in 1996, a trend that may or may not be real because of differing survey methods. On the Hudson Bay Lowlands (excluding the Pen Islands caribou) 8600 were reported in 1965, 7200 in 1989, 5500 in 1996, an apparent decline. The transitional forest populations has remained stable. Estimated caribou numbers inhabiting the true boreal forest have dropped from nearly 4000 in 1965 to 2700 in 1996, but this decrease was not confirmed by careful within-district breakdowns of sub-populations by habitat types and may be an artifact of classification from districts to regions. The sharpest decrease was reported for the Central Region, north east of Lake Superior, where estimates dropped from 500 in 1965 to 475 in 1989 and to 68 in 1996. Individual caribou bands approach recognized minimum numbers for isolated populations, and even totals by sub-population remain low: over 1300 in commercial forests, about 500 in potentially commercial forests, and 8-900 in parks. Due to small numbers in widely dispersed band-locations, the potential for human disturbance affecting these forest dwelling caribou is substantial.